GIANT CELL TUMOR OF TENDON SHEATH AT THE HAND: A CASE REPORT - Gwila, Mohamed; Jaralla, Ali; Chowdhury, Moniruddin; Humayra, Syeda (Bangladesh Journal of Multidisciplinary Scientific Research, 2022)
The study investigates the Giant Cell Tumor of Tendon Sheath (GCTTS), which is the second most prevalent soft tissue tumor after ganglion cysts. It is a benign nodular tumor found on the tendon sheath of the hands and feet. An atypical case of GCTTS with an abnormal location away from the tendon sheath has been reported. A 23-year-old Libyan man visited the Zliten Teaching Hospital with a history of first web space left-hand swelling since 6 months, increased in size, not tender on examination, hard mobile swelling not attached to underlying tissue, with the full range of motion in adjacent joints, and neurological deficit in the ulnar side of the thumb. The diagnosis was made clinically with a firm, nodular mass that does not transilluminate and had decreased signal intensity on both T1-and-T2-weighted MR imaging. Radiographic and histopathological examinations confirmed the benign nodular mass and the treatment modality. Marginal excision was performed and the tumor was completely removed to prevent a recurrence. JEL Classification Codes: H75.